(NsOWREMENNYJ RUSSKIJ QZYK (B:s (NsLOWOOBRAZOWANIE (B: (Nu^EBNOE POSOBIE (B/s - (NzEMSKAQ(B, (NeLENA aNDREEWNAs ((NmOSKWA (B:s (NpROSWE]ENIE(B,s, 1973)
(NsPISKI LIT(B. (NW KONCE GLAW(B.s
Keywords: (NrUSSKIJ QZYKs -- (NsLOWOOBRAZOWANIEs